Characterization Of Kenaf Bast Fibre Filled Poly(Butylene Succinate) Composites: Mechanical, Water Absorption And Weathering Properties - Thirmizir, Mohd Zharif Ahmad (2011)
Characterization of kenaf bast fibre (KBF) filled poly(butylene succinate) (PBS) composites in this study involved several stages. Firstly, the effect of KBF loadings (10 – 40 wt. %) on flexural and impact properties were investigated. The flexural strength of the composites increased with increasing fibre loadings up to 30 wt. % with the highest value of about 9.4 % before decreasing with a further increase in fibre loading. The flexural modulus of the composites increased about 87.1 – 424 % with increasing KBF loadings from 10 to 40 wt. %.